Ta`lîm Al-Lughat Al `Arabiat Li Al-Nâtiqîn Bighayrîha Fî Dûi Nazariât Al-Lughawiat Al-Nafsia - Humayro Toha; Rasyid Ridho; Uril Bahruddin (JP : JURNAL PENDIDIKAN, 2022)
A good education is based on appropriate educational theories, but many of those concerned with teaching the Arabic language did not employ these theories in their education process. This research aims to describe two things, (1) psychological theories related to teaching Arabic to non-native speakers, (2) a proposal to employ psycholinguistic theory in teaching Arabic. The research approach is qualitative, with the type of desk study, and the data is taken from books, magazines, and pamphlets related to the subject of the research, which were collected through observations and document studies. As for the analysis of the data, it was done by sorting, presenting and deducing from it. The results of the research are: The psychological theories related to teaching the Arabic language to non-native speakers are the behavioral theory, the structural theory, the cognitive theory, and the transformational generative theory. To the extent that helps achieve the objectives of teaching the Arabic language, and the conclusion of the research indicated that improving the process of teaching the Arabic language to non-native speakers is done by taking into account the appropriate theories.